THE EFFECT OF PROFITABILITY, LIQUIDITY, AND LEVERAGE ON TAX AGGRESSIVENESS - Mustika, Evitha Puspa; Nursiam, Nursiam (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study is a quantitative research aimed at analyzing the effects of profitability, liquidity, and leverage on tax aggressiveness in food and beverages companies listed on the Indonesia Stock Exchange (IDX) during the period of 2017-2022. Using purposive sampling, the study involved 18 companies as samples. Using multiple linear regression with the help of SPSS 24 software, the data have been analyzed. These findings uncover that the profitability has significant impact on tax aggressiveness with t-value of 2.150 which goes beyond the critical value of 1.98827 and a significant value of 0.034 (<5%) thus confirming H1. Additionally, liquidity substantially impacts tax aggressiveness where t-value is -2.450 which exceeded the critical value by -1.98827 and its significance was 0.016 (<5%) this confirm H2. On the contrary, Leverage had an adverse significant effect to Tax Aggressiveness as indicated by t-value of -4.136 being less than the critical value equal to -1.98827 and also had significance equal to 0.000 which is less than 5%, thus verifying the H3.